Isolamento, elucidação estrutural e avaliação da atividade antineuroinflamatória de novos sesquiterpenos de Anaxagorea dolichocarpa - Andrade, Rodrigo Silva de (2024)
Brazil, being the country with the greatest plant biodiversity in the world, has drawn scientific and technological interest, since most of the pharmaceutical industry's drugs come from plant species. Among these, Anaxagorea dolichocarpa Sprague & Sandwith (“paixinho”) stands out due to the isolated chemical constituents of pharmacological importance, such as alkaloids and sesquiterpenes, making it a promising species for continued studies. Thus, this work aimed to expand the phytochemical and pharmacological knowledge of this species. For this purpose, the roots of Anaxagorea dolichocarpa were collected in May 2021 in the municipality of Cruz do Espírito Santo – PB and were subjected to extraction and isolation processes by classical chromatographic methods and hyphenated techniques. The phytochemical study resulted in the isolation and identification of nineteen compounds, whose structures were unequivocally determined through the analysis of NMR, MS, and IR data, along with theoretical calculations of NMR (DP4+) and ECD. Eighteen novel macrocyclic humulene sesquiterpenoids, namely dolichocarpols G-X (1−18), were isolated, along with one previously known compound (nordine), whose structure was corrected in this work, and its absolute stereochemistry was determined by X-ray and ECD analysis. Furthermore, the compounds were tested for their cytotoxicity and antineuroinflammatory activity in the LPS/IFN-γ-stimulated BV2 cell line. Dolichocarpols G, K, N, O, and T, didn’t presented any cytotoxicity and effectively reduced NO levels in BV2 cells at concentrations ranging from 25 to 200 μM, reaching a maximum effect similar to that of the control (quercetin). Moreover, possible interactions between these compounds and the iNOS enzyme were predicted via in silico studies, and the results demonstrated that the compounds exhibited activity probability values greater than 0.5, which indicated their affinity for the target and that the formed complexes are stable, with low fluctuations in the tertiary structure of the enzyme. Therefore, these findings broadens the understanding of the structural diversity and biological activity of the macrocyclic humulene sesquiterpenoids from the Annonaceae family and the Anaxagorea dolichocarpa species, contributing to its phytochemical and pharmacological knowledge.